Audiovestibular system, fifth and seventh cranial nerve involvement in leprosy - Koyuncu, M.; Celik, O.; Ozturk, A.; Saunders, M. (My University, 1994)
Thirty-nine patients with leprosy and fifteen sex- and age-matched controls were investigated for disorders of the fifth and seventh cranial nerves and that of the audiovestibular system. Sensorineural hearing loss found to be of cochlear origin was detected in eight (22%) of the patients with leprosy compared to none in the control group (p > 0.05). Vestibular dysfunction was noted in four patients (11.1%) compared to none in the control group (p ? 0.05). Two cases were found to have fifth nerve involvement and one (2.8%) had seventh nerve involvement. None in the control group had fifth or seventh nerve deficit.
Keywords: Adult; Caloric Tests; Case-Control Studies; Facial Nerve; Female; Hearing Loss, Sensorineural; Human; Leprosy, Lepromatous; Male; Middle Age; Trigeminal Nerve; Vestibular Nerve; adult; article; audiovestibular system; controlled study; cranial nerve; female; hearing loss; human; leprosy; major clinical study; male